2007
DOI: 10.1002/tox.20270
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of pathological lesions induced by multiwalled carbon nanotubes in lungs of mice by intratracheal instillation and inhalation

Abstract: The pathological lesions induced by multiwalled carbon nanotubes (MWCNTs) in bronchi and alveoli of mice were studied by intratracheal instillation and inhalation. In instillation groups, the dose was 0.05 mg MWCNTs/mouse. Similar size clumps of MWCNTs were distributed in bronchi and alveoli. The clumps led to inflammation to the lining wall of bronchi and severe destruction to alveolar netted structure around them. In the inhalation groups, the mice were exposed to aerosolized MWCNTs with mean concentration o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
88
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 168 publications
(91 citation statements)
references
References 16 publications
3
88
0
Order By: Relevance
“…Results indicate that inhalation exposure resulted in 4-fold greater inflammation and fibrosis than aspiration of the same mass lung burden. Li et al 47 reported similar findings, that is, inhalation of a more dispersed MWCNT preparation caused greater interstitial fibrosis and cell proliferation than aspiration of a less dispersed preparation. Mercer et al 15 found that when efforts were made to improve the dispersion of aspirated SWCNT suspensions, fibrotic potency was similar between aspiration and a 4 day inhalation exposure.…”
Section: Relationships Between Bolus Pulmonary Exposure (It or Asmentioning
confidence: 75%
“…Results indicate that inhalation exposure resulted in 4-fold greater inflammation and fibrosis than aspiration of the same mass lung burden. Li et al 47 reported similar findings, that is, inhalation of a more dispersed MWCNT preparation caused greater interstitial fibrosis and cell proliferation than aspiration of a less dispersed preparation. Mercer et al 15 found that when efforts were made to improve the dispersion of aspirated SWCNT suspensions, fibrotic potency was similar between aspiration and a 4 day inhalation exposure.…”
Section: Relationships Between Bolus Pulmonary Exposure (It or Asmentioning
confidence: 75%
“…There are few studies that have developed aerosolization systems and delivered carbon-based nanomaterials via inhalation (Li et al 2007;Mitchell et al 2007;Ryman-Rasmussen et al 2008;Shvedova et al 2008). In the Mitchell et al (2007) study, MW-CNTs were aerosolized with a jet mill coupled to a dry chemical screw feeder and a 2-Āµm cut-point cyclone.…”
Section: Discussionmentioning
confidence: 99%
“…High percentages of early miscarriages and fetal malformations in female rats also have been reported following exposure to CNTs during pregnancy (Pietroiusti et al, 2011). In spite of adverse effects of CNTs, some investigations have reported that CNTs have no serious effect on various biological systems (Li et al, 2007;Garza et al, 2008;Bai et al, 2010;Wessels et al, 2011). The different outcomes following exposure to CNTs likely related to the types of CNTs, manipulation of CNTs (e.g., functionalizing of CNTs), physiology of exposed organism, posology and method of administration of CNTs.…”
Section: Introductionmentioning
confidence: 99%